2021
DOI: 10.3390/diagnostics11020358
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Fetal Left Ventricular Myocardial Performance Index (MPI) by Using an Automated Measurement of Doppler Signals in Normal Pregnancies

Abstract: The myocardial performance index is widely used as an indicator of the heart’s performance. However, due to the subjective nature of ultrasonic testing, there are differences in the measurements among inspectors, requiring a quantitative and objective assessment. In this study, an automated program was developed to quantitatively evaluate the myocardial performance index (MPI) and the cardiac time intervals in the left ventricle for each trimester. One hundred and thirty-three pregnant women who visited the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…With the introduction of routine use in automated methods, the relationship of MPI with fetal pathologies will be understood more clearly in the future. 31,32 Previous studies have reported that a learning process is required in order to perform accurate MPI measurements. For example, Cruz-Martinez et al 30 reported average numbers related to the completion of the learning process associated with left Mod-MPI measurements, such as 42 for ET, 77 for ICT, and 83 for IRT.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of routine use in automated methods, the relationship of MPI with fetal pathologies will be understood more clearly in the future. 31,32 Previous studies have reported that a learning process is required in order to perform accurate MPI measurements. For example, Cruz-Martinez et al 30 reported average numbers related to the completion of the learning process associated with left Mod-MPI measurements, such as 42 for ET, 77 for ICT, and 83 for IRT.…”
Section: Discussionmentioning
confidence: 99%
“…23 Hashemi et al Cases (24-40 weeks) with idiopathic mildly increased AFI Idiopathically, a slight rise in the amniotic fluid index (AFI) was linked to a big rise in the fetal MPI in both the left and right ventricles Ref. 24 Kim et al…”
Section: Ami Patientsmentioning
confidence: 99%
“…22 Idiopathically, a slight rise in the amniotic fluid index (AFI) was linked to a big rise in the fetal MPI in both the left and right ventricles. 23 Kim et al 24 made an automated way to recognize IVCT, IVRT, and ET and figure out the MPI so that the LV MPI of fetuses can be measured quantitatively and objectively with ultrasonic doppler. All tasks except data collection were done automatically, and the actual measurements of the same fetus were used to figure out the clinical value.…”
Section: Recent Studiesmentioning
confidence: 99%
“…As a non-invasive, pulsed-wave (PW) Doppler-derived measure of global myocardial function, it is currently used to evaluate fetal cardiac anatomy, hemodynamics and function [1]. By now, the Mod-MPI has been widely used to assess the function of the heart in a wide variety of pathological intrauterine conditions by estimating early fetal cardiac adaptive changes in complicated pregnancies, including fetal growth restriction (FGR), gestational diabetes, twin-to-twin transfusion syndrome (TTTS), congenital heart defects (CHD), pre-eclampsia, intrahepatic cholestasis of pregnancy (ICP) and other fetal intra-and extracardiac conditions [1,3,[17][18][19][20][21][22]. Ventricular dysfunction is associated with higher MPI values.…”
Section: Introductionmentioning
confidence: 99%